STRATEGI TOKOH AGAMA ISLAM MENINGKATKAN AKTIVITAS ORANGTUA MEMBERIKAN PENDIDIKAN AGAMA KEPADA ANAK - Darnawati Darnawati; Arnadi Arnadi; Alkadri (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research was motivated by the lack of parents in providing Islamic religious education to children. Therefore, Islamic religious leaders provide an understanding of Islam through parental activities. This study aims to obtain clear information about: 1) The strategy of Islamic religious leaders to increase parental activity in teaching prayers to children 2) The strategy of Islamic religious leaders to increase parental activity in teaching children to read the quran. This study uses a qualitative approach and a type of phenomenological research. The results showed that: 1) The strategy of Islamic religious leaders increased the activity of parents teaching children to pray (Study in Border areas) by: Islamic religious leaders conducting training and guidance to parents and children on how to pray, getting used to praying in congregation and both in the school environment and at home, Islamic religious leaders Provide programs for parents to increase prayer activities for children, Islamic religious leaders and parents provide mutual supervision of children in the teaching and learning process. 2) The strategy of Islamic religious leaders to increase parental activity in teaching children to read the quran (Study in Border Areas) by means of: Parents teaching children to read the quran, increasing children's concentration in learning to read the quran, parents Motivating Children to Interact in Lessons, parents motivating children who lack absorption in learning the quran, giving encouragement to children who lack discipline to learn the quran.